The impact of mandatory military service on labor outcomes. Evidence from Spain - Julio Cáceres Delpiano (Journal of Applied Economics)
Alternative for the abstract: Using Spanish data, I examine the impact of Military Service (MS) on labor outcomes for men born in 1968 and 1969. To address MS endogeneity, I use a national lottery as an instrumental variable (IV). Results show MS negatively affects various outcomes, depending on individuals’ work-life status at conscription. For men already in the workforce a year prior, IV estimates reveal significant impacts, particularly for those without mandatory education, notably reducing the likelihood of having a Social Security record. Among those entering the labor market post-lottery, Reduced Form estimates suggest an 8.5 percentage point reduction in employment and a 1.3-year decline in labor market experience. MS also leads to a 20% reduction in earnings, based on conservative estimates. Age-based analysis indicates MS effects extend beyond conscription years, highlighting broader implications beyond incapacitation.